CD1dhiPD-L1hiCD27+ Regulatory Natural Killer Subset Suppresses Atopic Dermatitis - Min, Keun Young; Koo, Jimo; Noh, Geunwoong; Lee, Dajeong; Jo, Min Geun; Lee, Ji Eon; Kang, Minseong; Hyun, Seung Yeun; Choi, Wahn Soo; Kim, Hyuk Soon (Frontiers in Immunology, 2022)
Effector and regulatory functions of various leukocytes in allergic diseases have been well reported. Although the role of conventional natural killer (NK) cells has been established, information on its regulatory phenotype and function are very limited. Therefore, the objective of this study was to investigate the phenotype and inhibitory functions of transforming growth factor (TGF)-β-producing regulatory NK (NKreg) subset in mice with MC903-induced atopic dermatitis (AD). Interestingly, the population of TGF-β-producing NK cells in peripheral blood monocytes (PBMCs) was decreased in AD patients than in healthy subjects. The number of TGF-β+ NK subsets was decreased in the spleen or cervical lymph node (cLN), but increased in ear tissues of mice with AD induced by MC903 than those of normal mice. We further observed that TGF-β+ NK subsets were largely included in CD1dhiPD-L1hiCD27+ NK cell subset. We also found that numbers of ILC2s and TH2 cells were significantly decreased by adoptive transfer of CD1dhiPD-L1hiCD27+ NK subsets. Notably, the ratio of splenic Treg per TH2 was increased by the adoptive transfer of CD1dhiPD-L1hiCD27+ NK cells in mice. Taken together, our findings demonstrate that the TGF-β-producing CD1dhiPD-L1hiCD27+ NK subset has a previously unrecognized role in suppressing TH2 immunity and ILC2 activation in AD mice, suggesting that the function of TGF-β-producing NK subset is closely associated with the severity of AD in humans.